LIVED EXPERIENCE OF FULL-TIME TEACHERS’ GRADUATE SCHOOLING DURING A PANDEMIC: Received: 13th September, 2021; Revised: 09th November 2021, 24th January 2022; Accepted: 21st February 2022 - Salubayba, Teodora Mabulay (PUPIL: International Journal of Teaching, Education and Learning, 2022)
This study portrays the unique experiences of graduate students in education during the pandemic and the commonalities of the interpretations and essences of those lived experiences. In the Philippines, some graduate students managed to survive in their full-time teaching and graduate education that was entirely remote online classes, where everything was home-based during the pandemic. Sixty-eight full-time teachers enrolled in the different graduate degree programs in education in one of the prestigious universities in the Philippines volunteered to share their stories via emails and informal audio-video chat. Commonalities among the unique and multiple realities of the experiences portray the essence of pandemic phenomenon like balance and equanimity for survival when everything was home-based, the importance of holding on to the lived values and personal traits as a stronghold, fortress, and strong weapon during the crisis, and a clear focus on finishing a graduate degree amidst pressing duties and responsibilities in full-time teaching, in the family, and graduate schooling. Findings suggest further inquiry on the graduate students’ lived experiences during a pandemic across cultures in various colleges and universities to uphold full-time teaching and graduate schooling toward efficient school leadership and governance during difficult times